2019
DOI: 10.1186/s12984-019-0560-6
|View full text |Cite
|
Sign up to set email alerts
|

Complexity based measures of postural stability provide novel evidence of functional decline in fragile X premutation carriers

Abstract: Background Fragile X Associated Tremor/Ataxia Syndrome (FXTAS) is a neurodegenerative movement disorder characterized by tremor, ataxic gait, and balance issues resulting from a premutation of the Fragile X Mental Retardation 1 (FMR1) gene. No biomarkers have yet been identified to allow early diagnosis of FXTAS, however, recent studies have reported subtle issues in the stability of younger premutation carriers, before disease onset. This study investigates the efficacy of multiscale entropy anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
0
10
1
Order By: Relevance
“…In agreement with these interpretations, experimental applications have demonstrated a degraded entropy in cardiac and postural dynamics associated with frailty, aging, impairments, or diseases [ 1 , 3 , 4 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. By contrast, high entropy is generally associated with an elevated capacity to adjust to an ever-changing environment [ 8 ], and elevated values are often observed in young healthy people [ 1 ].…”
Section: Introductionmentioning
confidence: 64%
“…In agreement with these interpretations, experimental applications have demonstrated a degraded entropy in cardiac and postural dynamics associated with frailty, aging, impairments, or diseases [ 1 , 3 , 4 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. By contrast, high entropy is generally associated with an elevated capacity to adjust to an ever-changing environment [ 8 ], and elevated values are often observed in young healthy people [ 1 ].…”
Section: Introductionmentioning
confidence: 64%
“…Atypical postural control has been demonstrated in premutation carriers without FXTAS, including increased postural sway when presented with conflicting visual information, implicating deficits in the integration of multi-sensory feedback inputs during motor behavior ( O'Keefe et al, 2015 ). Reduced complexity of postural sway also has been demonstrated and is associated with increased CGG repeat length in asymptomatic premutation carriers, indicating quantitative sensorimotor measurements may track with disease risk ( O'Keeffe et al, 2019 , Wang et al, 2019 ). Similarly, using tests of precision manual force, we recently documented increased motor variability in aging premutation carriers (between 44 and 77 years of age; Park et al, 2019 ) and reduced motor complexity associated with more severe clinical motor issues and increased CGG repeats ( McKinney et al, 2019 ).…”
Section: Introductionmentioning
confidence: 97%
“…In males, the studies based on MRI analyses revealed subtle changes in the integrity of white matter without, or prior to, the occurrence of FXTAS (Wang et al, 2012 , 2013 ; Battistella et al, 2013 ), and abnormal trajectories of cerebellar and brain stem volume loss from early adulthood (Wang et al, 2017 ). In female carriers, the findings of deficits on a range of tasks of executive functioning requiring rapid temporal responses (Shelton et al, 2016 ), or of subtle impairment of postural stability (O'Keeffe et al, 2019 ), compared with control non-carriers, suggested that there may be a slow but measurable decline in executive functioning and/or degradation of motor control in apparently asymptomatic individuals. The presence of intranuclear inclusions typical of FXTAS has been reported in both FXTAS and non-FXTAS female carriers (Tassone et al, 2012 ), and reinforces evidence for an accumulation of subclinical pathological processes over a broad age range associated with PM carriage.…”
Section: Introductionmentioning
confidence: 99%